Comparison of Inheritance Rights for Muslim Heirs in Indonesia and Malaysia: Islamic Law Perspective and Its Implementation - Firmansyah A, Debri (Universitas Negeri Gorontalo, 2024)
This study discusses the comparison of the granting of inheritance rights for Muslim heirs in Indonesia and Malaysia based on the perspective of Islamic law and its implementation in the national legal systems of each country. Islamic inheritance law in Indonesia is regulated in the Compilation of Islamic Law (KHI), the implementation of which is influenced by cultural diversity and the legal options given to the community. Meanwhile, in Malaysia, Islamic inheritance law is implemented through the Sharia Court which has exclusive jurisdiction to resolve inheritance cases for Muslims. This study uses a qualitative method with a descriptive-comparative approach to analyze the similarities and differences in the regulation and implementation of Islamic inheritance law in both countries. The results of the study show that although both countries base their inheritance law systems on sharia principles, differences in institutional structures and socio-political contexts result in variations in the implementation of the law. This study also identifies the challenges faced, such as differences in legal interpretation and conflicts between heirs, and provides recommendations to improve harmonization and efficiency in the implementation of Islamic inheritance law in Indonesia and Malaysia